The Influence of Solidarity on Employee Performance at the Department of Trade and Industry of Gowa Regency - Andika Ansari (Pustaka Digital Indonesia, 2023)
This research endeavor aims to delve into the impact of solidarity on employee performance within the Department of Trade and Industry in Gowa Regency. The chosen research methodology for this study is quantitative research. Data collection was meticulously carried out through the administration of well-structured questionnaires. The study's sample encompasses the entirety of the workforce within the Department of Trade and Industry in Gowa Regency. The sampling technique employed is known as saturation sampling, ensuring that every eligible participant is included in the study. Data were gathered through a combination of direct observation and the systematic distribution of questionnaires employing a Likert scale. The findings derived from this study convincingly demonstrate that solidarity exerts a positive and statistically significant influence on employee performance at the Department of Trade and Industry in Gowa Regency. These findings are substantiated by the results of the simple regression analysis, which yielded a coefficient of 0.412, and the t-test results, with a p-value of 0.040. In light of these substantial findings, it can be confidently concluded that solidarity indeed plays a pivotal role in shaping employee performance within the Department of Trade and Industry in Gowa Regency, underscoring its importance as a contributing factor in organizational effectiveness and efficiency..